Existence, Identity and Survive Strategy Kethoprak Tobong Kelana Bhakti Budaya - Inggit Sitowati (IJCAS (International Journal of Creative and Arts Studies), 2015)
Kethoprak Tobong Kelana Bhakti Budaya is one of Ketoprak tobong that still exist and survive from the onslaught of modern entertainment. Ketoprak tobong is a traditional Javanese theatrical art which performs and lives by moving from one place to another within a period of time. They maintain their existence because of their deep love for the Ketoprak world. In addition they have a sense of responsibility to preserve the nation’s cultural heritage by maintaining their tobong group. For them the Ketoprak world and tobong is their identity. The members of this group were born and grew up from the Ketoprak’s family and environment. The existence and identity of this group is formed from habitus, capital and field. For survive strategy, they apply the principles of kinship, flexibly apply the rules, looking for donors, and promotes the group through a variety of cultural events. To make ends meet they have other jobs, including craft, making costumes, makeup, and a singer in a wedding.